Soil moisture-atmosphere interactions drive terrestrial carbon-water trade-offs - Wenqi Sun; Sha Zhou; Bofu Yu; Yao Zhang; Trevor Keenan; Bojie Fu (Communications Earth & Environment)
Abstract Soil moisture is coupled with vegetation and atmosphere, influencing global cycling of water, carbon, and energy. However, it remains unclear how soil moisture-atmosphere interactions affect land-atmosphere carbon and water exchanges simultaneously. Using Earth system model experiments, we show widespread carbon-water trade-offs between net ecosystem production and precipitation-minus-evapotranspiration driven by soil moisture dynamics. Soil moisture positively controls net ecosystem production and negatively affects precipitation-minus-evapotranspiration, through direct soil water stress and indirect soil moisture-atmosphere feedbacks. While soil moisture variability magnifies the interannual variability of net ecosystem production, it moderates that of precipitation-minus-evapotranspiration over land. These opposing effects lead to a pronounced carbon-water trade-off, which originates from the interplay between carbon acquisition through photosynthesis and water extraction through evapotranspiration. This trade-off is projected to intensify in a warming and drying future, as soil moisture increasingly regulates carbon and water exchanges, posing a serious challenge to sustaining both terrestrial carbon sink and water supply.